Oxytocin and Health - Wu, Wei; Kostoglou-Athanassiou, Ifigenia (IntechOpen, 2021)
Oxytocin is a nonapeptide hormone with a central role in the regulation of parturition and lactation. Oxytocin receptors can be found in many tissues in humans. Oxytocin exerts a direct as well as an indirect effect on metabolism and energy balance. Considering the positive effects of oxytocin on the brain and the reproductive, immune, and autonomic nervous systems, it shows promise as a future treatment agent for anxiety, autism, personality disorders, and neurodegenerative disorders. This book focuses on oxytocin and health from the aspects of molecular and structure activity, physiological and pathological functions, and clinical applications.